2018
DOI: 10.1002/acr.23585
|View full text |Cite
|
Sign up to set email alerts
|

Tofacitinib in Rheumatoid Arthritis: Lack of Early Change in Disease Activity and the Probability of Achieving Low Disease Activity at Month 6

Abstract: In MTX-IR patients, lack of response to tofacitinib after 1 or 3 months predicted low probability of achieving LDA at month 6. Lack of early response may be considered when deciding whether to continue treatment with tofacitinib. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Nine 2-year-cycle data from the continuous NHANES (1999-2016) were combined for analysis with greater statistical reliability (n=92 062). We excluded men (n=45 336), participants younger than 18 years (n=19 087) or older than 80 years of age (n=919), [22][23][24][25] participants who had been diagnosed with other forms of arthritis, participants with missing RA data (n=3438) or dietary magnesium information (n=9958), and 13 324 participants were eventually included in the analysis (figure 1).…”
Section: Study Populationmentioning
confidence: 99%
“…Nine 2-year-cycle data from the continuous NHANES (1999-2016) were combined for analysis with greater statistical reliability (n=92 062). We excluded men (n=45 336), participants younger than 18 years (n=19 087) or older than 80 years of age (n=919), [22][23][24][25] participants who had been diagnosed with other forms of arthritis, participants with missing RA data (n=3438) or dietary magnesium information (n=9958), and 13 324 participants were eventually included in the analysis (figure 1).…”
Section: Study Populationmentioning
confidence: 99%
“…A post hoc analysis of two randomized, double-blind, Phase III studies explored early changes in disease activity and achievement of low activity and remission goals with tofacitinib. 21 In patients with an inadequate response to methotrexate, the lack of response to tofacitinib after one or three months predicted a low probability of achieving low disease activity by month six. 21 These results are important in guiding decision-making for continued treatment with tofacitinib in the face of a lack of early response, and stress the need to include this measurement early in the therapeutic evaluation of patients with RA.…”
Section: Discussionmentioning
confidence: 99%
“… 21 In patients with an inadequate response to methotrexate, the lack of response to tofacitinib after one or three months predicted a low probability of achieving low disease activity by month six. 21 These results are important in guiding decision-making for continued treatment with tofacitinib in the face of a lack of early response, and stress the need to include this measurement early in the therapeutic evaluation of patients with RA. Also, the multivariate analysis showed that the use of tofacitinib as first-line of treatment had a tendency toward significancy a lower response at six months but not at 12 months, showing that the use of tofacitinib achieves responses per year of treatment regardless of its use after conventional or biological therapy, as shown in other studies.…”
Section: Discussionmentioning
confidence: 99%
“… Effects of tofacitinib as monotherapy or in combination with csDMARD on (a) disease activity at Month 6, (b) patient-reported outcomes at Month 3, and (c) radiographic progression at Month 6 in phase III and IIIb/IV studies of patients with DMARD-IR. 6 8 , 14 , 47 50 , 82 , 85 …”
Section: Appropriate Use Of Tofacitinib At Different Stages In a Pati...mentioning
confidence: 99%